Entrepreneurial Capability and Ecosystem Synergy: A Strategic Alignment - Maralit, Irene H (International Journal of Basic and Applied Sciences, 2025)
The study aims to identify whether there is a relationship between an entrepreneur’s capability and the entrepreneurial ecosystem to develop a good strategy that would help an entrepreneur with decision-making. This would be beneficial to for them to realize the requirement to become successful entrepreneurs and for Batangas Province to realize the perfect environment for these entrepreneurs. The researcher employed a descriptive research method to collect the necessary data and information addressing the status of the study. The total number of respondents comprised 395 registered entrepreneurs from Batangas Province. To analyze the data and address the research objectives, various statistical tools were utilized, including Frequency/Percentage, Weighted Mean, One-Way Analysis of Variance (ANOVA), Brown-Forsythe test for non-homogeneous variances, and Pearson correlation. The findings revealed that most respondents were female, above 45 years old, married, and held a college degree. Regarding business profiles, most of the entrepreneurs operated establishments classified under the Wholesale and Retail Trade sector, employed 1–3 workers, and had been in operation for over 10 years. The assessment of entrepreneurial capability, measured in terms of sensing, selecting, shaping, and synchronizing, received a verbal interpretation of "Capable." Meanwhile, the entrepreneurial ecosystem, evaluated through dimensions such as policy, markets, human capital, support systems, culture, and finance, were rated as "favorable." A significant relationship was found between the entrepreneurial ecosystem and entrepreneurial capability, particularly in the aspect of sensing. A model was developed based on the results of the study.